2021
DOI: 10.1038/s41467-020-20524-2
|View full text |Cite
|
Sign up to set email alerts
|

The molecular make up of smoldering myeloma highlights the evolutionary pathways leading to multiple myeloma

Abstract: Smoldering myeloma (SMM) is associated with a high-risk of progression to myeloma (MM). We report the results of a study of 82 patients with both targeted sequencing that included a capture of the immunoglobulin and MYC regions. By comparing these results to newly diagnosed myeloma (MM) we show fewer NRAS and FAM46C mutations together with fewer adverse translocations, del(1p), del(14q), del(16q), and del(17p) in SMM consistent with their role as drivers of the transition to MM. KRAS mutations are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 37 publications
9
96
0
Order By: Relevance
“…More recent and larger sequencing efforts have confirmed several different point mutations in XBP1, mapping to different parts of the protein. Interestingly, these mutations are all missense or nonsense [6,19,20,116], have low clonal fraction and are absent in smoldering myeloma (SMM), suggesting that the loss of XBP1 is an "oncosuppressor-like" late event. Of note, initial clinical observations suggest that mutations in XBP1 predict resistance to PI-based therapies, thus confirming in vitro data on genetic manipulation of XBP1 [117].…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…More recent and larger sequencing efforts have confirmed several different point mutations in XBP1, mapping to different parts of the protein. Interestingly, these mutations are all missense or nonsense [6,19,20,116], have low clonal fraction and are absent in smoldering myeloma (SMM), suggesting that the loss of XBP1 is an "oncosuppressor-like" late event. Of note, initial clinical observations suggest that mutations in XBP1 predict resistance to PI-based therapies, thus confirming in vitro data on genetic manipulation of XBP1 [117].…”
Section: Accepted Articlementioning
confidence: 99%
“…Suggesting a MM-specific tumor suppressor role, FAM46C mutations are often coupled by loss of heterozygosity due to a deletion in the second allele [17,120]. A recent genetic study comparing mutations present in 82 SMM patients to newly diagnosed MM samples found significantly fewer FAM46C mutations and 1p deletions in SMM than MM, suggesting that FAM46C loss may be a defining event in the transition to active MM [116].…”
Section: Fam46c/tent5cmentioning
confidence: 99%
“…Furthermore, although to a lesser degree than the fully malignant counterpart, the genomic landscape of MGUS and SMM is still complex and heterogeneous. Only with the recent application of NGS techniques, and in particular whole-genome sequencing (WGS), it was possible to have a more complete picture of the lesions involved in SMM progression [8,[23][24][25], capturing also structural variants (SVs) and complex genomic aberrations involving non-coding sequences, which play a key role as disease drivers [26,27]. In particular, WGS, in addition to having uncovered an unprecedented catalog of MM driver events, has allowed estimating the timeline in which they are acquired during disease progression.…”
Section: Genomic Landscape and Intrinsic Determinants Of Smm Progressionmentioning
confidence: 99%
“…Two recently published NGS-based studies provide a comprehensive view of the genetic make-up of SMM [8,24]. Both studies highlighted that, overall, SMM has a similar genetic landscape to newly diagnosed MM.…”
Section: Genomic Landscapementioning
confidence: 99%
See 1 more Smart Citation